Microorganisms for green revolution. Volume 1, - Panpatte, Deepak G.; Jhala, Yogeshvari K.; Vyas, R. V.; Shelat, H. N. (Springer, 2017)
This book addresses basic and applied aspects of two nexus points of microorganisms in agro-ecosystems, namely their functional role as bio-fertilizers and bio-pesticides. Readers will find detailed information on all of the aspects that are required to make a microbe "agriculturally beneficial." A healthy, balanced soil ecosystem provides a habitat for crops to grow without the need for interventions such as agro-chemicals. No organism in an agro-ecosystem can flourish individually, which is why research on the interaction of microorganisms with higher forms of life has increasingly gained momentum in the last 10-15 years. In fact, most of plants' life processes only become possible through interactions with microorganisms. Using these "little helpers" as a biological alternative to agro-chemicals is a highly contemporary field of research. The information presented here is based on the authors' extensive experience in the subject area, gathered in the course of their careers in the field of agricultural microbiology. The book offers a valuable resource for all readers who are actively involved in research on agriculturally beneficial microorganisms. In addition, it will help prepare readers for the future challenges that climate change will pose for agriculture and will help to bridge the current gaps between different scientific communities.
Keywords: Agricultural microbiology.; Sustainable agriculture.; elektronické knihy; electronic books